Echocardiographic analysis of dogs before and after surgical treatment of brachycephalic obstructive airway syndrome - Brložnik, Maja; Nemec Svete, Alenka; Erjavec, Vladimira; Domanjko Petrič, Aleksandra (Frontiers in Veterinary Science, 2023)
Brachycephalic dogs with brachycephalic obstructive airway syndrome (BOAS) are a valuable animal model for obstructive sleep apnea (OSA) in humans. Surgical treatment of BOAS improves clinical signs of upper airway obstruction; however, the effect of surgery on cardiac morphology and function has not been studied. Therefore, we aimed to compare the echocardiographic variables of dogs before and after surgical treatment of BOAS. We performed a complete echocardiographic examination in eighteen client-owned dogs with BOAS (7 French Bulldogs, 6 Boston Terriers, and 5 Pugs) scheduled for surgical correction. Follow-up echocardiographic examinations were performed 6 to 12 (median 9) months after surgical treatment. The control group consisted of seven non-brachycephalic dogs. After surgery, BOAS patients had a significantly (p < 0.05) larger left atrium to aortic ratio (LA/Ao), left atrium in the long axis index, and thickness of the left ventricular posterior wall in diastole index. They also had a higher late diastolic annular velocity of the interventricular septum (Am) and increased global right ventricular strain and left ventricular global strain in the apical 4-chamber view, as well as a higher caudal vena cava collapsibility index (CVCCI). Before surgery, BOAS patients had a significantly lower CVCCI, Am, peak systolic annular velocity of the interventricular septum (Si), and early diastolic annular velocity of the interventricular septum (Ei) compared to non-brachycephalic dogs. After surgery, BOAS patients had a smaller right ventricular internal diameter at base index, right ventricular area in systole index, mitral annular plane systolic excursion index, and tricuspid annular plane systolic excursion index, as well as lower values of Am, Si, Ei, and late diastolic annular velocity of the interventricular septum, and a larger LA/Ao compared to non-brachycephalic dogs. Significant differences between BOAS patients and non-brachycephalic dogs suggest higher right heart pressures and decreased systolic and diastolic ventricular function in BOAS dogs, consistent with findings in OSA patients. In parallel with the marked clinical improvement, right heart pressures decreased, and right ventricular systolic and diastolic function improved after surgery.